Investigation on the Radar Scattering and Doppler Spectrum From Trimaran Based on the Motion of Six Degrees of Freedom - Yuxin Deng; Jinxing Li; Wangqiang Jiang; Min Zhang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The trimaran is an advanced ship with high hydrodynamic performance, but the study of its electromagnetic characteristics and Doppler spectrum is insufficient. This study presents a new procedure for evaluating the scattering echo and Doppler spectrum of a trimaran in a time-varying ocean environment. First, based on the Reynolds-averaged Navier–Stokes equations, the interpolation wave-making method is proposed for the prediction of the six degrees of freedom motion of the trimaran. The method takes into account the viscous effect of the flow field and the complexity of wave motion, which applies to the seakeeping prediction of high-speed trimaran under different sea states. Second, an accelerated geometrical optics and physical optics algorithm using the light source function (GO-PO/LSF) is proposed, which uses the light source function to realize the visibility judgment of surfaces and greatly reduces the computation time. Then, the influence of different motion conditions on the backscattering echo of the composite scene is demonstrated by the capillary wave modification facet scattering model and GO-PO/LSF. Finally, the Doppler spectrum characteristics of the trimaran are presented by the standard spectrum estimation method, which provides a reference for radar detection and identification of ships in the microwave band.